Observation of the Y(4230) and a new structure in *Supported in part by National Key R&D Program of China (2020YFA0406300, 2020YFA0406400); National Natural Science Foundation of China (NSFC) under Contracts Nos. (11625523, 11635010, 11735014, 11822506, 11835012, 11935015, 11935016, 11935018, 11961141012, 12022510, 12025502, 12035009, 12035013, 12061131003); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS under Contracts Nos. (U1732263, U1832207); CAS Key Research Program of Frontier Sciences under Contract No. (QYZDJ-SSW-SLH040); 100 Talents Program of CAS; INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC under Contract No. (758462); European Union Horizon 2020 research and innovation programme under Contract No. Marie Sklodowska-Curie grant agreement No (894790); German Research Foundation DFG under Contracts Nos. (443159800), Collaborative Research Center CRC 1044, FOR 2359, GRK 214; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey under Contract No. (DPT2006K-120470); National Science and Technology fund; Olle Engkvist Foundation under Contract No. (200-0605); STFC (United Kingdom); The Knut and Alice Wallenberg Foundation (Sweden) under Contract No. (2016.0157); The Royal Society, UK under Contracts Nos. (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy under Contracts Nos. (DE-FG02-05ER41374, DE-SC-001206). (1st November 2022) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, X. H. 旭红; Bai 白, Y. 羽; Bakina, O.; Baldini Ferroli, R.; et al.
Abstract: The cross sections of at center-of-mass energies from 4.127 to 4.600 GeV are measured based on 15.6 fb data collected with the BESIII detector operating at the BEPCII storage ring. Two resonant structures are observed in the line shape of the cross sections. The mass and width of the first structure are measured to be ( ) MeV and ( ) MeV, respectively. They are consistent with those of the established . The second structure is observed for the first time with a statistical significance greater than 8 σ, denoted as . Its mass and width are determined to be ( ) MeV and ( ) MeV, respectively. The first presented uncertainties are statistical and the second ones are systematic. The product of the electronic partial width with the decay branching fraction is reported.